2016
DOI: 10.1371/journal.pone.0150138
|View full text |Cite
|
Sign up to set email alerts
|

ADAM15 Is Functionally Associated with the Metastatic Progression of Human Bladder Cancer

Abstract: ADAM15 is a member of a family of catalytically active disintegrin membrane metalloproteinases that function as molecular signaling switches, shed membrane bound growth factors and/or cleave and inactivate cell adhesion molecules. Aberrant metalloproteinase function of ADAM15 may contribute to tumor progression through the release of growth factors or disruption of cell adhesion. In this study, we utilized human bladder cancer tissues and cell lines to evaluate the expression and function of ADAM15 in the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Our results also showed that the inhibited expression of ADAM15 via miR-3174 significantly reduced the proliferation and metastasis of the patient-derived bladder cancer cells. These results were consistent with previous results from Lorenzatti et al 34 Interestingly, our results show that the expression of ADAM23 in the tumor tissue was lower compared to the non-tumor tissue. Also, the expression of ADAM28 and ADAM33 in the tumor tissue was slightly lower compared to the non-tumor tissue, although no statistical significance was found.…”
Section: Discussionsupporting
confidence: 94%
“…Our results also showed that the inhibited expression of ADAM15 via miR-3174 significantly reduced the proliferation and metastasis of the patient-derived bladder cancer cells. These results were consistent with previous results from Lorenzatti et al 34 Interestingly, our results show that the expression of ADAM23 in the tumor tissue was lower compared to the non-tumor tissue. Also, the expression of ADAM28 and ADAM33 in the tumor tissue was slightly lower compared to the non-tumor tissue, although no statistical significance was found.…”
Section: Discussionsupporting
confidence: 94%
“…Bladder cancer is a highly prevalent tumor and is related to substantial morbidity, mortality and cost [ 1 , 2 , 49 ]. The environmental or occupational exposures to carcinogens, particularly tobacco, are the major risk factors for promoting the bladder cancer [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human bladder cancer is one of the most common genitourinary malignant cancers, leading to health issue worldwide [ 1 , 2 ]. Presently, the existed therapeutic strategies, including radical cystectomy and chemotherapy, are far from to be satisfied considering the metastases and recurrence of human bladder cancer [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, high throughput functional siRNA screening identified molecules associated with protein degradation, such as Furin, ADAMs, and CAPN ( Supplementary Figure 1 ), as therapeutic targets. For example, ADAM15 is overexpressed in bladder, prostate and breast cancers and its substrate include EGFR ligands and TGF-β that are related to cancer cell proliferation [ 39 ]. These results suggest that protein degradation may be essential for proteins synthesized by deregulated c-Myc to perform their oncogenic functions, as we have indicated with Furin (Figure 4G ).…”
Section: Discussionmentioning
confidence: 99%